Built Environments, Constructed Societies. - Vis, Benjamin (Sidestone Press, 2009)
Archaeology, as the discipline that searches to explain the development of society by means of material remains, has been avoiding the big issues involved with its research agenda. The topic of social evolution is concealed by anxiety about previous paradigmatic malpractice and the primary archaeological division of the world in culture areas still suffers from the archaic methods by which it was established. Archaeological inference of developing societies is weighed down by its choice of particularism within agency approaches and overtly reductionist due to the prevalence of statistical, cla.